Peran Sektor Industri Pengolahan dalam Pertumbuhan Ekonomi di Daerah Kabupaten Deli Serdang - Rangga Wardana; Lailan Syafrina Hasibuan; Wina Nurfitriani; Jhon Martin Putra Siregar (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2026)
The manufacturing sector occupies a strategic position as a primary driver of regional economic growth, generating added value, creating employment opportunities, and reinforcing the structural foundation of the regional economy. This study examines the contribution of the manufacturing sector to the economic development of Deli Serdang Regency over the 2020–2024 period. A quantitative descriptive approach was employed, drawing on time-series secondary data from the Central Statistics Agency (BPS) of Deli Serdang Regency, regional planning documents, and Gross Regional Domestic Product (GRDP) figures by industrial classification. Analysis was conducted through calculation of sectoral contribution ratios and trend interpretation across the observation period. Findings reveal that the manufacturing sector contributed approximately 15.17 percent of Deli Serdang Regency’s GRDP in 2024 (Rp22,971.29 billion out of Rp151,451.40 billion total), supported by 763 small and medium industry (SMI) units, and has maintained an upward trajectory despite a brief contraction in 2021, notwithstanding a temporary deceleration during the pandemic. Beyond its GRDP contribution, the sector plays a pivotal role in workforce absorption, particularly through small and medium-sized industries that harness local resource endowments. Its interconnections with agriculture, trade, and transportation generate a multiplier effect that bolsters the region’s economic resilience.